Human Quercetin Conjugated Metabolites Attenuate TNF-α-induced Changes in Vasomodulatory Molecules in an HUASMCs/HUVECs Co-culture Model - Lodi, Federica; Winterbone, Mark S.; Tribolo, Sandra; Needs, Paul W.; Hughes, David A.; Kroon, Paul A. (Planta Medica, 2012)
There is accumulating evidence from epidemiological and human intervention studies that quercetin-rich diets can protect against cardiovascular diseases. Quercetin glycosides are modified during metabolism, and the forms reaching the systemic circulation are glucuronidated, sulfated, and methylated. The aim of this study was to analyse the potential beneficial effects of quercetin and its conjugated metabolites on vascular function on a co-culture model of human umbilical artery smooth muscle cells and human umbilical vein endothelial cells. We observed that physiologically relevant metabolites of quercetin were able to reduce ET-1 protein and gene expression and to increase accumulation of cGMP in TNF-α-induced HUASMCs co-cultured with HUVECs. This is the first study to demonstrate an ability of quercetin and its conjugated metabolites, at physiologically achievable concentrations, to modulate vascular function in a co-culture model comprising human vascular endothelial and smooth muscle cells.
Keywords: quercetin conjugated metabolites; human vascular smooth muscle cells; human vascular endothelial cells; endothelin-1; cGMP